Emotional Meaning in Context in Relation to Hypomanic Personality Traits: An ERP Study. - Sarah Terrien; Pamela Gobin; Alexandre Coutté; Flavien Thuaire; Galina Iakimova; Pascale Mazzola-Pomietto; Chrystel Besche-Richard (PLoS ONE, 2015)
The ability to integrate contextual information is important for the comprehension of emotional and social situations. While some studies have shown that emotional processes and social cognition are impaired in people with hypomanic personality trait, no results have been reported concerning the neurophysiological processes mediating the processing of emotional information during the integration of contextual social information in this population. We therefore chose to conduct an ERP study dealing with the integration of emotional information in a population with hypomanic personality trait. Healthy participants were evaluated using the Hypomanic Personality Scale (HPS), and ERPs were recorded during a linguistic task in which participants silently read sentence pairs describing short social situations. The first sentence implicitly conveyed the positive or negative emotional state of a character. The second sentence was emotionally congruent or incongruent with the first sentence. We analyzed the difference in the modulation of two components (N400 and LPC) in response to the emotional word present at the end of the "target" sentences as a function of the HPS score and the emotional valence of the context. Our results showed a possible modulation of the N400 component in response to both positive and negative context among the participants who scored high on the Mood Volatility subscale of the Hypomanic Personality Scale. These results seem to indicate that the participants with hypomanic personality traits exhibited specificities in the integration of emotions at the level of the early-mobilized neurocognitive processes (N400). Participants with hypomanic personality traits found it difficult to integrate negative emotional contexts, while simultaneously exhibiting an enhanced integration of positive emotional contexts.